2001
DOI: 10.1038/sj.leu.2401983
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of MOZ and p300 histone acetyltransferases in acute monocytic leukemia with a t(8;22)(p11;q13) chromosome translocation

Abstract: Histone acetyltransferase p300 functions as a transcriptional co-activator which interacts with a number of transcription factors. Monocytic leukemia zinc finger protein (MOZ) has histone acetyltransferase activity. We report the fusion of the MOZ gene to the p300 gene in acute myeloid leukemia with translocation t(8;22)(p11;q13). FISH and Southern blot analyses showed the rearrangement of the MOZ and p300 genes. We determined the genomic structure of the p300 and the MOZ genes and the breakpoints of the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(106 citation statements)
references
References 19 publications
1
105
0
Order By: Relevance
“…MOZ-CBP lacks the SM domain of MOZ, but gains almost all of CBP (Figure 3a). Mirroring the homology between p300 and CBP, the MOZ gene is fused to that of p300 in translocation t(8;22)(p11;q13) (Chaffanet et al, 2000;Kitabayashi et al, 2001b). Moreover, in t(10;16)(q22;p13) associated with childhood AML or therapeutic myelodysplastic syndromes, the MORF gene on 10q22 (Champagne et al, 1999) is fused to that of CBP (Panagopoulos et al, 2001;Kojima et al, 2003).…”
Section: Moz and Morf In Leukemia Leiomyomata And Other Malignanciesmentioning
confidence: 99%
“…MOZ-CBP lacks the SM domain of MOZ, but gains almost all of CBP (Figure 3a). Mirroring the homology between p300 and CBP, the MOZ gene is fused to that of p300 in translocation t(8;22)(p11;q13) (Chaffanet et al, 2000;Kitabayashi et al, 2001b). Moreover, in t(10;16)(q22;p13) associated with childhood AML or therapeutic myelodysplastic syndromes, the MORF gene on 10q22 (Champagne et al, 1999) is fused to that of CBP (Panagopoulos et al, 2001;Kojima et al, 2003).…”
Section: Moz and Morf In Leukemia Leiomyomata And Other Malignanciesmentioning
confidence: 99%
“…Recent biochemical purifications revealed that both the Drosophila and mammalian MOF proteins reside in multi-protein complexes and that most of these interacting proteins are conserved between Drosophila and mammals (Table 2; Dou et al, 2005;Smith et al, 2005;Mendjan et al, 2006). Co-purification of four human MSL proteins (hMSL1, hMSL2, hMSL3 and hMOF) showed that the MSL (Borrow et al, 1996;Carapeti et al, 1998;Champagne et al, 1999Champagne et al, , 2001Chaffanet et al, 2000;Kitabayashi et al, 2001;Pelletier et al, 2002;Bristow and Shore, 2003;Deguchi et al, 2003;Kindle et al, 2005;Katsumoto et al, 2006;Thomas et al, 2006;Ohta et al, 2007 Abbreviation: HAT, histone acetyltransferases.…”
Section: The Histone Acetyltransferase Mofmentioning
confidence: 99%
“…1::8p11.2→8q13::8q22→8qter),add(19)(p13.3) (Kitabayashi et al, 2001;Tasaka et al, 2002). Hybrid/Mutated gene Monocytic leukemia zinc finger gene (MOZ, Gene EP300 (E1A binding protein p300) Negri G, Gervasini C Atlas Genet Cytogenet Oncol Haematol.…”
Section: Cytogeneticsmentioning
confidence: 99%
“…All MOZ fusion partner genes are involved in histone modification and transcriptional regulation (Katsumoto et al, 2008). To date, only three cases of t(8;22)(p11;q13) involving MOZ and EP300 have been reported and investigated at DNA and RNA levels in two of them (Lai et al, 1992;Soenen et al, 1996;Chaffanet et al, 2000;Kitabayashi et al, 2001;Tasaka et al, 2002). In Chaffanet et al, and in Kitabayashi et al, MOZ-EP300 fusion genes result from the hybrid junction between exon 16 and exon 15 of MOZ with exons 2 and 3 of EP300, respectively.…”
Section: Cytogeneticsmentioning
confidence: 99%